THERMAL MANAGEMENT AT THE ENERGY WATER ENVIRONMENT NEXUS: FROM PHOTOTHERMAL MATERIALS AND BUILDING ENVELOPES TO GRIDRESPONSIVE ENERGY SYSTEMS - Djamalu, Yunita; Djafar, Romi; Fauziah, Siti; Pakaya, Roys (Program Vokasi-Universitas Negeri Gorontalo, 2025)
Thermal phenomena sit at the heart of today’s most important sustainability challenges, producing clean water, maintaining healthy indoor climates, valorizing biomass, and balancing increasingly variable power grids. This review synthesizes state-of-the-art advances across materials, devices, buildings, and energy systems to outline an integrated research agenda for the energy–water–environment nexus. We highlight photothermal platforms for desalination and wastewater treatment, including macroporous three-dimensional MXene architectures with high broadband absorption and near-complete contaminant rejection, a nature-inspired “suspended” evaporator that resists salt accumulation even in 15–20 wt% brines, and scaling-mitigating slippery membranes for robust membrane distillation (Lan, Wood, & Yuen, 2019), (Zhao et al., 2019), (Islam et al., 2020). For the built environment, we analyze optimization of phase-change Trombe walls, localized solid-state humidity pumping, evidence-based thermal comfort indices, and holistic multi-objective design of net-zero energy housing in the tropics (Zhang et al., 2022; Tumuluru, Ghiasi, Soelberg, & Sokhansanj, 2021), (Luo et al., 2021; Mani et al., 2023). On the supply side, we assess rapid load transitions in solid-oxide-fuel-cell–gas-turbine hybrids, optimization-driven power-flow management, and thermal-pollution constraints on water-cooled generation (Staiger, Laschewski, & Matzarakis, 2019),(Zhu et al., 2021; Li, Hua, Tu, & Wang, 2019). Finally, we connect circular carbon strategies torrefaction and biochar to both energy quality and environmental remediation (Karanikola, Boo, Rolf, & Elimelech, 2018), (Miara et al., 2018). We conclude with cross-cutting gaps in durability, field validation, and multi-scale modeling, and propose harmonized metrics and standardized protocols to accelerate translation. All citations derive from the user-provided corpus.